Wild shore : exploring Lake Superior by kayak - Breining, Greg. (Minneapolis : University of Minnesota Press, 2000)
Over two years, sportsman, writer, and world traveler Greg Breining set out to circle Lake Superior by kayak, a means of travel that allowed him to visit the lakes places of rare beauty and solitude, experience its wildly varied moods, and see its remote historic sites and isolated communities. Wild Shore is a tale of outdoor adventure, odd characters, humorous stories, and quiet reflection.
East Shore: Sault Sainte Marie to Old Woman Bay -- Pukaskwa Peninsula: Michipicoten River to Hattie Cove -- Coldwell Peninsula: Little Pic River to Port Coldwell -- Slate Islands -- Nipigon Islands: Rossport to Pigeon River -- Minnesota: Pigeon River to Duluth -- Isle Royale -- Apostle Islands: Brule Point to La Pointe -- South shore: Long Island to Houghton -- Keweenaw Peninsula: Houghton to Marquette -- Pictured Rocks: Grand Island to Brimley State Park.
Includes bibliographical references (pages 259-263).
Print version record.
JSTOR
Keywords: Kayak touring -- Superior, Lake; Superior, Lake -- Description and travel; Canoë-kayak -- Supérieur, Lac; Supérieur, Lac -- Descriptions et voyages; Randonnée nautique -- Supérieur, Lac; TRAVEL -- General; LITERARY CRITICISM -- General; Kayak touring; Travel; Lake Superior